2015
DOI: 10.3390/rel6041263
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religion among Sex Workers in Thailand

Abstract: This qualitative research seeks the understanding of the role of religion in the lives of sex workers in Thailand. It is based on interviews conducted among sex workers working in karaoke bars in Bangkok. Findings show that most sex workers experience different levels of life difficulty. The level of life difficulty also affects the experience of internal conflicts regarding sex and morality. Finally religion has been used as a form of ritual purification in dealing with internal sense of conflicts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Thailand has always been a religious country. Religion and spirituality are believed to be a fundamental part of who we are as human beings (Siroj and Brenitez, 2015). Studies of contemporary Thai sexuality often examine Buddhist scriptures and practices that denote non-heteronormative behaviors (Jackson and Dejnakarintra, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thailand has always been a religious country. Religion and spirituality are believed to be a fundamental part of who we are as human beings (Siroj and Brenitez, 2015). Studies of contemporary Thai sexuality often examine Buddhist scriptures and practices that denote non-heteronormative behaviors (Jackson and Dejnakarintra, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This query poses as a question an opinion known in the literature as a “rape myth” and represents one of many false beliefs people hold about sexual assault that shift blame from the perpetrator to the survivor. Although most studies (see Cotton et al, 2002; Jakobsson & Kotsadam, 2011) seem to imply there should be a positive correlation between acceptance of rape myths and thinking it is morally acceptable to buy and sell sex, in the context of a Bolivian society overfilled with macho culture 20 and where almost 90% of people identify as Christians, 21 the relationship may work in reverse—people may believe women who dress provocatively are to blame if they are sexually abused (a consequence of macho culture, described in Ugarte et al, 2003; Wilson, 2014) and think transactional sex is immoral and should be illegal at the same time (a consequence of religion, described in Sorajjakool & Benitez, 2015; Vaggione, 2018).…”
Section: Datamentioning
confidence: 99%
“…Sex work is generally considered unacceptable in mainstream Thai society and is also condemned by the dominant Buddhist culture. Sex work by its nature is not in connection with morality (Sorajjakool andBenitez 2015, p. 1270). Kirsch (1982) pointed out four decades ago that Thai women were more attached to the 'this-worldly' domain than their male counterparts, based on an observation that the majority of market sellers were women, indicating their greed and materialism.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Peace has even suggested that Buddhism's broadly positive perception of sex workers explains why prostitution, despite being regarded as both illegal and immoral, is still widely accepted in Thailand. Sorajjakool and Benitez (2015), in their study of 12 sex workers in Bangkok, describe how sex workers adopt Buddhist teachings and practices to reconcile their inner conflict and moral qualms about their occupation. In short, the relationship between sex workers and Buddhism may not be one of simple opposition.…”
Section: Introductionmentioning
confidence: 99%